2017
DOI: 10.1037/abn0000304
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of ovarian steroid hormones on alcohol use and binge drinking across the menstrual cycle.

Abstract: Patterns and features of substance use and abuse vary across the menstrual cycle in humans. Yet, little work has systematically examined the within-person relationships between ovarian hormone changes and alcohol use across the menstrual cycle. Our study was the first to examine the roles of within-person levels and changes in estradiol (E2) and progesterone (P4) in relation to daily alcohol use and binge drinking in young women. Participants were 22 naturally-cycling women, ages 18–22, recruited through a uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 61 publications
4
37
1
Order By: Relevance
“…The course of PME is less well-defined than PMDD, but generally follows similar pattern in which symptoms peak in the late luteal phase and show improvement in the mid-to-late follicular phase (see gradient in Figure 1). Of note, in addition to worsened symptoms prior to menses, addictive disorders may show a primary or secondary worsening around ovulation, when surging estradiol increases reward sensitivity (e.g., Martel, Eisenlohr-Moul, & Roberts, 2017).…”
Section: Perimenstrual Exacerbation (Pme) Of Underlying Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…The course of PME is less well-defined than PMDD, but generally follows similar pattern in which symptoms peak in the late luteal phase and show improvement in the mid-to-late follicular phase (see gradient in Figure 1). Of note, in addition to worsened symptoms prior to menses, addictive disorders may show a primary or secondary worsening around ovulation, when surging estradiol increases reward sensitivity (e.g., Martel, Eisenlohr-Moul, & Roberts, 2017).…”
Section: Perimenstrual Exacerbation (Pme) Of Underlying Disordersmentioning
confidence: 99%
“…Many small (N<50) longitudinal studies have observed main effects of the cycle on symptom severity in various mental disorders, suggesting the likelihood that females diagnosed with those disorders are similarly at risk for (though not necessarily suffering from) PME. These disorders include bulimia nervosa (Edler, Lipson, & Keel, 2007), borderline personality disorder (Eisenlohr-Moul, DeWall, Girdler, & Segerstrom, 2015; Eisenlohr-Moul et al, 2018)), obsessive-compulsive disorder (Vulink, Denys, Bus, & Westenberg, 2006), bipolar disorder (Dias et al, 2011;Teatero, Mazmanian, & Sharma, 2014), schizophrenia (Seeman, 2012), substance abuse (Martel et al, 2017), and post-traumatic stress disorder (Nillni et al, 2015). Of note, a longitudinal study in bipolar disorder demonstrated that patients with PME of bipolar (vs. those females with bipolar without PME) suffered a more severe and chronic course of illness (Dias et al, 2011).…”
Section: Premenstrual Disorders 12mentioning
confidence: 99%
“…After a primary peak of P4 and a secondary peak of E2 levels, both E2 and P4 withdraw premenstrually and a new cycle begins. Longitudinal and experimental work shows that the menstrual cycle can modulate affective and behavioral outcomes (e.g., [21][22][23][24]) as well as physiological functions, like nutritional metabolism (e.g., [25,26]) and vagally-mediated HRV (e.g., [27]). Intra-individual variations in vagally-mediated HRV across the menstrual cycle with their potential implications for female daily functioning and well-being have therefore been the subject of various empirical studies.…”
Section: Introductionmentioning
confidence: 99%
“…The biological factors that contribute to binge drinking by women are not well understood, although ovarian hormones, specifically estrogen (17b-estradiol, E2), may play a role. Circulating E2 levels in women are positively associated with alcohol consumption (Muti et al, 1998;Martin et al, 1999;Martel et al, 2017), and numerous alcohol drinking studies in female rodents have demonstrated that E2 administration increases alcohol drinking (Ford et al, 2002a;Marinelli et al, 2003;Reid et al, 2003;Ford et al, 2004;Quirarte et al, 2007;Rajasingh et al, 2007;Satta et al, 2018a). Understanding the molecular and cellular mechanisms of action of E2 in enhancing ethanol drinking is important for developing new approaches to reduce excessive drinking by women.…”
Section: Introductionmentioning
confidence: 99%